Ignorance : literature and agnoiology - Bennett, Andrew, 1960 December 2- (Manchester : Manchester University Press, 2009)
This text offers a new theory of & new ways of thinking about literature, with insights into literary theory. It offers an important rethinking of Romanticism & its influence on literary studies, from the 19th century to the present. It includes new readings of a range of authors including Wordsworth, Dickens & Seamus Heaney.
9780719074875; 9780719074875; Copyright Page; Contents; Acknowledgements; Introduction; 1 Ignorance and philosophy; 2 Literary ignorance; 3 To see as poets do:Romanticism, the sublime and poetic ignorance; 4 The opposite of epistemology:Keatsian nescience; 5 Our ignorance of others:Middlemarch and Great Expectations; 6 Joseph Conrad's blindness; 7 Children, deathand the enigmatic signifier:Wordsworth and Bowen; 8 Monsters and trees:epistemelancholia in David Hume and Henry James; 9 American ignorance:Philip Roth's American trilogy; 10 The politics of authorial ignorance:contemporary poetry.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: English literature -- 19th century -- History and criticism; English literature -- 20th century -- History and criticism; Ignorance (Theory of knowledge) in literature; Littérature anglaise -- 19e siècle -- Histoire et critique; Littérature anglaise -- 20e siècle -- Histoire et critique; Ignorance dans la littérature.; Literature: History & Criticism; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- General; English literature; Ignorance (Theory of knowledge) in literature; 1800-1999; Criticism, interpretation, etc; Anthologies